2004
DOI: 10.1111/j.1600-0889.2004.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of crustal microparticles from Chilean Patagonia to the Antarctic Peninsula by SEM-EDS analysis

Abstract: The individual elemental composition of insoluble airborne particulates found in King George Island (KGI), Antarctic Peninsula (atmosphere, snow, firn and ice deposits) and in the atmosphere of Chilean Patagonia by SEM‐EDS analysis identify probable sources and transport mechanisms for the atmospheric aerosols observed in these regions. Insoluble airborne particulates found in the snow, firn and ice in a core from Lange Glacier (KGI) call for significant crustal influence, mainly associated with aluminium pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Evangelista et al () and Kanitz et al () made observations of dust during cruises in transit over the SW Atlantic. Evidence of long range transport is suggested by the observations of recent (spanning last decades) findings of dust in snow of the Antarctica Peninsula (McConnell et al, ; Pereira et al, ) and East Antarctica (Bory et al, ; Laluraj et al, ). Recently, Hooper et al () reported the presence of recent (last decade) deposition of dust in the east flank of a glacier in South Georgia Island directly downwind of Patagonia.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Evangelista et al () and Kanitz et al () made observations of dust during cruises in transit over the SW Atlantic. Evidence of long range transport is suggested by the observations of recent (spanning last decades) findings of dust in snow of the Antarctica Peninsula (McConnell et al, ; Pereira et al, ) and East Antarctica (Bory et al, ; Laluraj et al, ). Recently, Hooper et al () reported the presence of recent (last decade) deposition of dust in the east flank of a glacier in South Georgia Island directly downwind of Patagonia.…”
Section: Introductionmentioning
confidence: 97%
“…The objective is to provide a general view of dust activity with a data set of surface and satellite observations collected daily and spanning almost 50 years. Results are aggregated at monthly and yearly resolutions so future studies can compare these observations with dust records found in snow in Antarctica that have similar time resolutions (Pereira et al, ; McConnell et al, ; Laluraj et al, ; Hooper et al, ). Section provides a description of the area of interest, section details the databases utilized, section provides an analysis and interpretation of the surface observation, and section incorporates the satellite data into the surface observation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This area is interesting for water resources, as the source of the Heihe River, the second largest inland river of China. However, little literature has comprehensively focused on snow chemistry and atmospheric circulation in this region, although the aerosol particles deposited in snow/ice have been well recognized as an important medium and can provide valuable information on environmental changes (Pereira et al, 2004;Cong et al, 2009). In this study, factor and correlation analysis are employed to examine chemical composition and the temporal variation of major ions in the Shiyi Glacier.…”
Section: Introductionmentioning
confidence: 99%
“…Pereira [2002] and Pereira et al [2004], employing SEM‐EDS microanalysis of insoluble particulates from a deep ice core from King George Island/South Shetland Archipelago and in the Chilean Patagonia atmosphere found out that 95% of continental dust in the north of the Antarctic Peninsula could be explained by the atmospheric transport from Patagonia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent measurements of deuterium/hydrogen ratios and 3 H in snow, firn and ice of a 60 m ice core from the island suggested an average annual precipitation rate of 0.63 m y −1 [ Pereira et al , 2004] and estimates in the past for the area indicated around 0.4 m y −1 [ Schwerdtfeger , 1970]. The exposed terrain is only a minute fraction of the total ice‐covered island area, with less than 1%, distributed mainly along the coastline and steep slopes.…”
Section: Introductionmentioning
confidence: 99%